A PROPOSED SYLLABUS OF CRITICAL READING FOR THE ENGLISH DEPARTMENT STUDENTS OF BRAWIJAYA UNIVERSITY - Emy Sudarwati (Erudio Journal of Educational Innovation, 2013)
The purpose of this study is developing an appropriate Critical Reading  syllabus for English department students of Brawijaya university. This study uses Research and Development design with a procedure which consists of  needs analysis, description of the purpose, selection or development of syllabus type, production of proto syllabus, production of pedagogical syllabus expert validation, evaluation and revision, try out, final product. The final version of the product consists of Critical Reading syllabus. The product has been developed by following the stages in the modified Yalden’s model   Keywords:  critical reading, syllabus